Initiative to Utilize Information Technology for Community Based Platform to Promote Innovative Government in Indonesia (The Indonesian Journal of Business Administration, 2012)
In current circumstances, innovation is becoming a mandatory requirement, both in private and public sectors. While it is more a common word for practices in private sector, the implementation in public sector faces several tougher challenges. Most people perceive public sectors as bureaucratic, rigid, heavily regulated and have limited space for new ideas. These perception then cause the people’s skepticism on innovation in their government.The above condition also happened in Indonesia. Although the Government of Republic of Indonesia has initiated and communicated to the public several innovative programs in various sectors, most people still have limited awareness on the progress.This project focuses on identifying and designing effort to build an interactive communication channel to promote the implementation of innovative government in Indonesia. The channel is positioned as a community based initiative, independent and utilizing information technology and social media. In order to maintain its independency, this project is needed to be professionally managed and have a sustainable operation scenario. Keywords: Innovative Government, Community Based, Independent, Sustainable